2001
DOI: 10.1103/physrevlett.87.185001
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Transport Cross Phase by Strongly Sheared Flow

Abstract: A generic model for advection of a scalar by E 3 B flow with a linearly varying mean shows that the cross phase factor in the transport flux is strongly reduced in the strong shear regime (shearing rate . eddy turnover rate), leading to significant transport suppression. The cross phase scales much more strongly with shear strength than do fluctuation amplitudes, allowing significant transport reduction even if fluctuations increase, or decrease only slightly. Cross-phase suppression thus can be the dominant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
72
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 19 publications
7
72
0
Order By: Relevance
“…A reduction of 30 % was observed in the phase of maximum ZF amplitude which was sustained beyond the lifetime of the ZF. In agreement with theory [34,35], it was shown that the turbulent transport reduction is initially induced by a modification of the cross phase between density and potential fluctuations and later maintained by reduced fluctuation amplitudes. The findings underline the importance of ZFs as a trigger for global confinement phenomena like the transition from L-to H-mode.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…A reduction of 30 % was observed in the phase of maximum ZF amplitude which was sustained beyond the lifetime of the ZF. In agreement with theory [34,35], it was shown that the turbulent transport reduction is initially induced by a modification of the cross phase between density and potential fluctuations and later maintained by reduced fluctuation amplitudes. The findings underline the importance of ZFs as a trigger for global confinement phenomena like the transition from L-to H-mode.…”
supporting
confidence: 85%
“…3 reaches zero. Thus, in the early phase of the ZF the cross phase α nE rather than the turbulent amplitudes is relevant for transport reduction as it was already emphasized in theoretical [34,35] works. Also biasing experiments indicated that shear flows mainly act on the cross phase [36,37,25].…”
mentioning
confidence: 78%
“…Models based on radial decorrelation of turbulent structures by sheared flow are prevalent in the theoretical literature [16][17][18][19][20][21][22][23][24][25] and provide a number of predictions concerning the quantitative scaling of turbulent quantities with shear. The basic premise underlying these models is the competition between linear or nonlinear turbulence dynamics and the tendency of sheared flows to "rip apart" or decorrelate turbulent structures; this leads to reduced fluctuation amplitude and decreased radial transport step-size.…”
Section: Introductionmentioning
confidence: 99%
“…This flux can be decreased due to either a reduction in the amplitude of any of the fluctuating fields 4 or to an appropriate shift in the phase between advected and advecting fields. 12 The details of how this suppression happens are however often complicated and still not well understood in many cases. Mostly for that reason, the investigation of these various possibilities in a tokamak geometry is traditionally done by assuming ab initio that some effective diffusivity can be used to characterize radial transport in the absence of any poloidal ͑and toroidal͒ flow.…”
Section: Introductionmentioning
confidence: 99%